New Perspectives on Electric Vehicles - Găiceanu, Marian (IntechOpen, 2022)
Modern transportation systems have adverse effects on the climate, emitting greenhouse gases and polluting the air. As such, new modes of non-polluting transportation, including electric vehicles and plug-in hybrids, are a major focus of current research and development. This book explores the future of transportation. It is divided into four sections: "Electric Vehicles Infrastructures," "Architectures of the Electric Vehicles," "Technologies of the Electric Vehicles," and "Propulsion Systems." The chapter authors share their research experience regarding the main barriers in electric vehicle implementation, their thoughts on electric vehicle modelling and control, and network communication challenges.